Don't read this book before dinner! : revoltingly true tales of foul food, icky animals, horrible history, and more - Claybourne, Anna (National Geographic kids., 2019)
Collects true stories of human waste, rodents and bugs, unsanitary habits, and foul-smelling subjects. Includes color photographs from "National Geographic," facts, and quizzes.